TINGKAT TEKNOLOGI LOGAM DALAM MASYARAKAT PENDUKUNG BUDAYA SITUS PASIR ANGIN - R.r. Triwurjani; Sudarti Prijono (Berkala Arkeologi, 1998)
The variety of types and the number of metal crust findings indicate that at the site there has been a metalworking activity, this is also supported by the variation in the composition of each mixture. The variation of the mixture that is made shows that the people who support the Pasir Angin culture have mastered knowledge of metal alloys. The technique used in the manufacture of bronze artifacts generally still uses the casting technique, with molds made of a mixture of sand and clay, while the forging technique is thought to be still at an experimental stage.